Predição de epidemias causadas por Phakopsora pachyrhizi em soja - Lerner, Maíne Alessandra (2019)
The main strategy to control Asian rust (Phakopsora pachyrhizi) is the chemical control along with the use of disease risk prediction models which would help in the decision making. The studies aimed to validate a scoring system based on rain, air temperature, sowing times and soybean phenological stages. The scoring system was used to determine the risk of occurrence of Asian soybean rust and to be a tool for decision making of the first fungicide application. Experiments were carried out in the field crops in 2015/16, 2016/17 and 2017/18 in Itaara/RS, with different sowing times and different cultivars. In addition, a spore trap was installed in December 2015 at the experimental area in order to monitor the fluctuation of the spore area of Phakopsora pachyrhizi. In the first study, conducted during 2015/16 and 2016/17 growing seasons, the objective was to validate the levels of risk of occurrence of Asian rust determined through the scoring system at different sowing times. The results indicated that the medium / high risk level was the most adequate to start the fungicide applications. In the second study, conducted during the 2016/17 and 2017/18 period, the objective was to validate the use of the scoring system in different soybean cultivars, which presented different levels of pathogen sensitivity. The results indicated that the proposed system was reliable even on different soybean cultivars. In the third study, conducted in the period from December 2015 to January 2019, the objective was to identify the correlation of wind directions and Phakopsora pachyrhizi spores dispersal. According to the results, north and northwest wind directions can explain the origin of the inital incolum to the southern areas.